Inventarisasi Jenis-Jenis Anggrek di Sekitar Danau Kalimpaa Kawasan Taman Nasional Lore Lindu Sulawesi Tengah - Fahlil Fahlil; Syamsurizal M Sulaeman; Ramadhanil Pitopang (Biocelebes, 2018)
Research about the “Inventory of Orchids around Kalimpaa Lake, Lore Lindu National Park ”, Sedoa Village, Lore Utara district, Poso regency, Central Sulawesi, has been conducted from May to June 2016, which aims to determine of orchids species and host tree. The method of collecting data and sample conducted a survey include exploration in the field without ignoring the abiotic factors include temperature and humidity. While, the precipitation data were obtained from Institution of Meterologi, Klimatologi and Geofisika Palu. Identification conducted in the field and biodiversity laboratory. Based on the identification obtained 13 genera consists of 21 species of orchids, 15 is an epiphyte orchids grow at 6 species of host tree and 6 others are type of orchids that terrestrial grow. Inculude genera Agrostophyllum, Arundina, Bulbophyllum, Calanthe, Coelogyne, Dendrobium, Eria, Liparis, Malasix, Oncidium, Phaius, Rhomboda. 6 host tree species of orchids that is, Castanopsis accuminatisima, Poliosma celebica, Vaccinium sp, Cisoceton sp, Ficus sp dan Glocidion sp.